바디롤러 운동과 요가의 복합처치가 중년여성 요통환자의 체력, 척추 변인 및 통증자각도에 미치는 영향 - 박해연; 김진홍; 강설중; 김병로 (The Asian journal of kinesiology, 2015)
[PURPOSE] The purpose of this study was to investigate the effect of combined intervention of body roller exercise and yoga on physical fitness, variables relate vertebral column of middle aged women with chronic lower back pain. [METHODS] Forteen middle-aged women with chronic low back pain were divided into one of two groups, i.e., exercise group (n=7, age 59.0±7.4 years) and control group (n=7, age 53.1±8.5 years). Subjects in exercise group went through body roller exercise and Yoga for 40 min and 20 min per session, respectively. Yoga exercise was Trikonasana; Adho Mukha Svanasana; Bhujangasana; Supta Padangusthasana1, 2, 3; Eka Padaanda Rajakapotasana. The physical fitness, Cobb's angle, lumbar spine rotation, tilt shoulders, pelvis horizontal degrees, visual analogue scale (VAS) were measured and compared between pre- and post test. [RESULTS] Muscular endurance was significantly higher after the intervention compared in the exercise group. Lumbar spine rotation length, shoulder slope, VAS were significantly decreased after the intervention in exercise group. However, no significant interactions were observed in flexibility, Cobb's angle, and pelvis height. [CONCLUSIONS] Body rollers exercise and Yoga intervention improved positively in muscular endurance, spine rotation angle, tilt shoulders, and the VAS Index. In conclusion, data suggest that body rollers exercise and Yoga may be an effective intervention for patients with low back pain. KCI Citation Count: 0